2009
DOI: 10.1111/j.1440-1754.2008.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Do no more harm: The psychological stress of the medical examination for alleged child sexual abuse

Abstract: Aim: Currently, there is some controversy that the medical examination following allegations of child sexual abuse may further traumatise the child. Access for children to appropriate care may be hindered if decisions about referral are influenced by personal beliefs, rather than by recognition of the potential health and psychological benefits of the assessment. We aimed to study the expectations and emotional responses of children and their parents to the medical examination. Methods:We conducted a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
1
20
2
Order By: Relevance
“…Furthermore, understanding of the examination purpose and procedure) was associated with caregiver anxiety. Unlike previous research (e.g., Marks et al, 2009), we found that greater understanding of the exam procedure was significantly related with increased report of caregiver anxiety prior to the examination. One possible explanation could be that caregivers who are aware of the exam procedure (child needing to undress, examination of genitals) may experience increased anxiety at the thought of their child undergoing examination.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Furthermore, understanding of the examination purpose and procedure) was associated with caregiver anxiety. Unlike previous research (e.g., Marks et al, 2009), we found that greater understanding of the exam procedure was significantly related with increased report of caregiver anxiety prior to the examination. One possible explanation could be that caregivers who are aware of the exam procedure (child needing to undress, examination of genitals) may experience increased anxiety at the thought of their child undergoing examination.…”
Section: Discussioncontrasting
confidence: 85%
“…These results indicate that further research is needed in order to examine factors associated with different racial/ethnic groups that may contribute to anxiety during the examination. Furthermore, parental education level is one factor that has been shown in the literature to be associated with distress during the CSAME (Marks et al, 2009) that could also influence understanding of the examination purpose and procedures and should be taken into consideration in intervention development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this finding is consistent with Sayfan et al (2008)'s finding that children alleging sexual abuse were more "upset" during investigative interviews than children alleging other types of abuse. Perhaps sexual abuse itself is more stressful (Maikovich, Koenen, & Jaffee, 2009;Marks, Lamb, & Tzioumi, 2009;Vyssoki & Schuermann-Emanuely, 2008;Werner & Werner, 2008) or more difficult to discuss in investigative settings than other types of abuse (Alaggia, 2004;Keary & Fitzpatrick, 1994;Lippert, Cross, & Jones, 2009;London et al, 2008).…”
Section: Discussionmentioning
confidence: 99%